Evaluation of Dentists' Involvement in Children's Public Insurance Programs - Alshammeri , Anoud saleh; alshammari, Seham saad; al enezy , Tamam lafi; albilasi, Rakan menwer; Alruwili, Faydhah madani; al abbas, Fatimah mohmmed jawad saleh; alenzy , Rahaf mohmmed; alanazi , Fawziah abdullah; alsadun, Miran saud; Alsalmi , Hajer Aiydh; Hejazi , Lama; Al-Otaibi , Majed Salman; et al. (Journal of Ecohumanism, 2024)
Background: Access to dental care for children covered by public insurance programs . Rural areas face particularly pronounced challenges due to dentist shortages and lower participation in public insurance programs. Previous studies have explored dentist participation in public insurance programs but have not adequately addressed differences between rural and urban areas, or among dental practice types. Methods: This study analyzed data from Dentists were categorized by location (rural, suburban, or urban), practice type (general, pediatric, or specialist), and public insurance participation . Data were matched and classified using rural-urban commuting area (RUCA) codes. Statistical analyses were conducted to compare participation rates and geographic disparities, with results visualized at city and county levels. Results: Among the 225,300 dentists analyzed, urban areas had the highest concentration of dentists (84%) but the lowest public insurance participation rates . Rural areas had fewer dentists (5%) but exhibited higher participation rates . Pediatric dentists showed the highest public insurance participation, whereas general dentists and specialists had significantly lower rates. Variability in participation was observed at city and county levels, with disparities reaching up to 100% in certain counties. Conclusion: Significant disparities in dentist availability and participation , particularly in rural areas and among non-pediatric dentists. City -level policies, such as joint administration, expanded loan forgiveness programs, and school-based dental services, are essential to improve access. Tailored, localized interventions are necessary to address geographic and professional disparities and ensure equitable pediatric dental care access.